Reconstruction of Dalihan Na Tolu in Batak Culture Towards a Practical Theology Relevant to the Task of the Church - Rahmat Hasudungan Nainggolan; Binur Panjaitan; Arip Surpi Sitompul (PT Inovasi Pratama Internasional, 2023)
The role of Dalihan na tolu is something that cannot be separated in the life of the Toba Batak indigenous people. In his role with the task of the church, Dalihan na tolu can go hand in hand in proclaiming the truth of God's Word so that customs and Christianity become one and form new habits, new customs, which are based on the love of Christ. The problem that will be discussed is the reconstruction of Dalihan na tolu in Batak culture towards practical theology that is relevant to the task of the church. The approach method used in this research is a qualitative research method, while the research approach used is a qualitative research approach with the technique of